Organizational knowledge and technology an action-oriented perspective on organization and information systems - Magalhães, Rodrigo 1950- (Edward Elgar, 2004)
This book attempts to make sense of a new area of integrated study, namely information systems and information technology (IS/IT) and the organization. It also aims to bring this mix into the broader theme of complexity as applied to organization and management and to draw useful conclusions about how to organize and how to manage IS/IT in the knowledge era. The author argues in favour of a more action-oriented--as opposed to planning dominated--approach to information systems management